ثنائية البيانات الضخمة والذكاء الاصطناعي لتحقيق التنمية المستدامة على المستوى الدولي - دراسة تحليلية - حمرة, يسرى; دراجي, أسماء (University of Eloued جامعة الوادي, 2022)
This study aims to identify the role of big data and artificial intelligence duality in achieving sustainable development in countries. The study has shown the existence of a complementary relationship of big data and artificial intelligence from scientific prespectif. The results of UNO 2020 report confirms the existence of a high positif impact of this duality on achieving sustainable development goals, with achieving 63% of economic goals, 79% social, and 93% of ecological ones. It was shown that countries use big data to evaluate sustainability goals in medium manner, despite to its tardiness related to Covid-19 pandemic. The study results with a set of recommendations that can more encourage decision makers in adopting both of big data and artificial intelligence in enhancing the trend of sustainable development.
The duality of Big Data (BD) and Artificial Intelligence (AI) in achieving a sustainable development in international level -Analytic study-
مداخلة. الملتقى الدولي الافتراضي حول: البيانات الضخمة والاقتصاد الرقمي كآلية لتحقيق الإقلاع الاقتصادي في الدول النامية "الفرص، التحديات والآفاق"
Keywords: البيانات الضخمة، الذكاء الاصطناعي، التعلم الآلي، التنمية المستدامة; Big Data; Artficial intelligence; Machine learning; Sustainable development.